PENGARUH BENTUK PENILAIAN FORMATIF TERHADAP HASIL BELAJAR IPA SETELAH MENGONTROL PENGETAHUAN AWAL SISWA - Muh. Ilyas Ismail (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2012)
This research aims at identifying the effect of formative assessment type towards the learning achievement of Natural Sciences. This study applied 2 x 2 factorial design experimental methods. The population of the research was all the fift grade students of elementary school number 03 and 05 of Rawamangun Eastern Jakarta, with 80 students as sample, implementing inferential statistic assessment with ANCOVA. The result of the study showed that (1) having controlled the students' prior knowledge, the learning achievement of Natural Sciences of the group, which was given essay test formative assessment was different from the achievement of those with multiple choice test, (2) having controlled the students' prior knowledge, the learning achievement of Natural Sciences of the group which was given essay test formative assessment was higher than the group in multiple choice test.